Strategy Management of Dakwah Education in the Era of the Industrial Revolution 4.0 - Atep Jalaludin; Ulfiah Ulfiah; Achmad Mudrikah; Sayyid Rifki Noval (Journal of Social Science, 2021)
challenges to the da'wah movement and da'wah education in the very complex industrial 4.0 era, including; Da'wah runs very normatively, does not pay attention to the actual situations that exist in society, da'wah runs stagnant and is unable to answer real problems in society, and there is still a lack of application of da'wah strategies, including da'wah that involves a da'wah organization. Therefore, there is a need for strategic management of da'wah and da'wah education, so that the existence of da'wah is not displaced in this 4.0 industrial era. The purpose of this research in general is to obtain an overview, describe, and reveal this research. The focus of the specific objectives is to obtain an overview of 1) environmental analysis, 2) strategy formulation, 3) strategy implementation, 4) evaluation and control, and 5) supporting and inhibiting factors of this research. The research procedure uses qualitative methods, through the process: 1) Observation; 2) Interview; 3) Documentation. Which was developed through the triangulation process, processed using descriptive logic analysis. The findings of this study include 1) environmental analysis carried out in two stages, namely: internal environmental analysis which includes components of strengths and weaknesses that are owned and faced, and external environmental analysis with two main components, namely opportunities and challenges/threats, 2) strategy formulation is carried out systematically. systematic with elements consisting of vision, mission, goals, policies, and main strategies in the application of this research. 3) strategy implementation is the process of realizing a strategy formulation which includes programs, budgets, and procedures, 4) evaluation and control of the program implementation of this research is a control measure from the start of the program being compiled, then implemented and the program ends, and 5) human resources (HR) is a factor supporting the implementation of this research and the mindset of the management who still doesn't understand is the obstacle.